Coping Strategies for Public Speaking Anxiety in EFL Learners: A Study of EDSA English Study Club Members - Muhibbah, Lilik; Zulhi Amalia, Taranindya (J-SHMIC : Journal of English for Academic, 2025)
This study examines Public Speaking Anxiety (PSA) among EDSA English Study Club members, which hinders their ability to perform English-based public speaking activities. PSA is influenced by individual and group factors, potentially affecting members' self-development and English-speaking skills if left unaddressed. Effective mentoring and techniques are essential to alleviate anxiety and enhance public speaking abilities. Implementing training focused on coping strategies serves as a complementary measure, enabling participants to optimize their performance, particularly during discussions. This study, conducted using an action research approach, involved 22 participants through structured questionnaires and personal reflections. Results indicated that the most frequently employed coping strategies were relaxation (22.7%) and well-preparedness (18.2%), with well-preparedness identified as the most effective (27.3%). Additionally, 90.9% of participants reported a reduction in PSA. Despite their potential benefits, positive visualization and gradual exposure were underutilized. The findings highlight the importance of structured interventions, cultural considerations, and long-term resilience-building for managing PSA effectively in EFL contexts.